The College Students' Psychosocial Problems in The Covid-19 Pandemic Era: The College Students' Psychosocial Problems in The Covid-19 Pandemic Era - Henry Wiyono (Jurnal Ilmu Keperawatan Jiwa, 2023)
The coronavirus disease (COVID-19) pandemic is a severe problem for all residents in various countries. The impact of the pandemic is very detrimental to all existing segments of life, without exception the education aspect. Many countries have decided to divert teaching and learning activities to online methods both at the school and university level, including in Indonesia, to prevent the spread of the COVID-19 disease. Psychological health problems often occur such as anxiety, fear, depression and even insomnia at all levels of society, including students. This study aims to determine the description of psychosocial problems such as depression, anxiety and stress in students in several cities in Indonesia who carry out online learning during the COVID-19 pandemic outbreak. This study uses a quantitative descriptive design, using an online survey research design, the sampling technique used is stratified random sampling with a sample of 400 respondents based on the specified inclusion criteria. Data were collected using the Depression Anxiety Stress Scale (DASS-21) instrument. Univariate data analysis using frequency distribution in the form of percentages. The results showed that 157 students (66%) of 238 students experienced moderate category anxiety, 81 students (75%) out of 108 experienced mild depression and 44 students (81%) out of 54 experienced mild stress. based on the results of this study found an increase in psychosocial problems, especially anxiety in students during online learning so the role of lecturers must be good at modifying learning techniques that can be accepted by students.